1998
DOI: 10.1002/(sici)1099-0682(199811)1998:11<1765::aid-ejic1765>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Stability of Zirconium(IV) Complexes with Hydroxy Ions

Abstract: A protometric study on the speciation of zirconium(IV) was performed in an aqueous solution at 25 °C in KNO3 and four ionic strengths (0.2, 0.5, 1, and 2 mol·dm−3). This study indicates the formation of the soluble species Zr(OH)3+, Zr2(OH)7+, and Zr(OH)4 in the pH range 1.5–3.5. The use of an appropriate titration technique allows the precipitation of the zirconium hydroxide to be limited. The overall stability constants βmlh of these three hydroxo complexes were computed and refined, by the program PROTAF, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
297
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(303 citation statements)
references
References 17 publications
6
297
0
Order By: Relevance
“…This behavior is supported by the results of Brown et al [26] for thorium hydrolysis, where evidence was found for the species Th(OH) 3+ , Th 6 (OH) 15 9+ and Th 4 (OH) 12 4+ . In the present study, the data support the formation of the U 4 (OH) 12 4+ species but not the U 6 (OH) 15 9+ species (Table 2). However, this result may not be entirely surprising.…”
Section: +supporting
confidence: 73%
See 3 more Smart Citations
“…This behavior is supported by the results of Brown et al [26] for thorium hydrolysis, where evidence was found for the species Th(OH) 3+ , Th 6 (OH) 15 9+ and Th 4 (OH) 12 4+ . In the present study, the data support the formation of the U 4 (OH) 12 4+ species but not the U 6 (OH) 15 9+ species (Table 2). However, this result may not be entirely surprising.…”
Section: +supporting
confidence: 73%
“…In a recalculation of this work, Baes and Mesmer [17] found that the data were consistent with the formation of U(OH) 3+ and U 6 (OH) 15 9+ but that systematic deviations remained at high pH values. These deviations point to the need for an additional species that has a q/p ratio higher than 2.5 at these higher pH values [17].…”
Section: +supporting
confidence: 54%
See 2 more Smart Citations
“…In order to operate efficiently as 'pH-swing' extractants for Zr IV , loading and stripping, e.g., L org þ Zr 4þ ½ZrðL-4HÞ org þ 4H þ ðL ¼ 1Þ 2L org þ Zr 4þ ½ZrðL-2HÞ 2 org þ 4H þ ðL ¼ 3 or 4Þ must occur over a pH-range to allow the ligand to be fully loaded at a pH lower than that at which insoluble zirconium(IV) oxy/hydroxides precipitate from aqueous solution [10], and be fully stripped at a low pH which is conveniently accessible with hydrochloride or similar acids. Ligand 1 was synthesised by a modified literature procedure [8] outlined in Scheme 1.…”
mentioning
confidence: 99%